A "Portrait" of Book XII of the Æneid: the Mosaic of the «House of the Medusa» (Alter do Chão, Portugal) - Caetano, Maria Teresa (2014)
This paper addresses the study of a mosaic discovered in 2007 at the archaeological site of Alter do Chão, Portugal, whose central panel represents the penultimate scene narrated in the last Book of the Æneid – a Roman epic composed by the poet Publius Vergilius Maro (70 BC – AD 19), at the request of Gaius Julius Cæsar Octavianus Augustus (63 BC – AD 14): it shows the very moment when Turnus, the Latin king of the Rutuli, kneels before Æneas, considered the precursor to the foundation of Rome (Virgil, Æneid, XII, 926-950).